THE CONSTRUCTION OF THE INDEPENDENCE STRUGGLE NARRATIVE IN SENIOR HIGH SCHOOL HISTORY TEXTBOOKS UNDER THE MERDEKA CURRICULUM: A CRITICAL DISCOURSE ANALYSIS - Sartika, Lianda Dewi; Dewanta, Anak Agung Ngurah Bagus Janitra; Alqadri, Bagdawansyah (Jurnal Historica, 2026)
The narrative of the 1945 independence struggle in history textbooks plays a crucial role in shaping students’ understanding of national identity. However, its presentation does not always reflect the diversity of historical perspectives or meet the demands of critical learning. This study aims to analyze the construction of the 1945 independence narrative in high school history textbooks under the Merdeka Curriculum. The study employs a qualitative approach using a three-dimensional critical discourse analysis framework encompassing textual analysis, social context, and the underlying perspectives of the narrative. Data were drawn from two history textbooks for Grades 11 and 12 published by the Ministry of Education. The units of analysis included narrative texts, illustrations, learning activities, and assessment questions related to the theme of independence. The results indicate that the narrative is predominantly shaped by a nationalist perspective that emphasizes the role of elite figures, while the contributions of other groups are only partially represented. Furthermore, most assessment questions remain focused on factual recall and do not sufficiently promote critical thinking skills. These findings reveal a gap between the intended curriculum and the actual presentation of material in textbooks. Therefore, the development of more inclusive, analytical, and contextualized historical narratives is necessary to support critical history learning.